Bringing Antonovsky's salutogenic theory to life: A qualitative inquiry into the experiences of young people with congenital heart disease. Issue 1 (1st January 2016) - Apers, Silke; Rassart, Jessica; Luyckx, Koen; Oris, Leen; Goossens, Eva; Budts, Werner; Moons, Philip; for the I-DETACH Investigators,
Abstract : Objective: Antonovsky coined sense of coherence (SOC) as the central concept of his salutogenic theory focusing on the origins of well-being. SOC captures the degree to which one perceives the world as comprehensible, manageable, and meaningful. Life events and resources are considered to be the building blocks of a person's SOC. However, mainly quantitative studies have looked into the role of life events and resources. Therefore, the present study aims to gain a deeper insight into the experiences of patients with congenital heart disease (CHD) regarding resources and life events. Method: For this qualitative study, patients were selected from the sample of a preceding study on development of SOC ( n = 429). In total, 12 young individuals with CHD who had either a weak ( n = 6) or strong SOC ( n = 6) over time were interviewed (8 women, median age of 20 years). Data analysis was based on the constant comparative method as detailed in the Qualitative Analysis Guide of Leuven. Commonalities and differences between patients from both groups were explored. Results: The following themes emerged: (1) self-concept; (2) social environment; (3) daytime activities; (4) life events and disease-related turning points; (5) stress and coping; and (6) illness integration. Additionally, the degree of personal control was identified as an overarching topic that transcended the other themes when comparing both groups of patients. Conclusion: These results may have implications for the structure and content of interventions improving well-being in young people with CHD.